Penggunaan Modul Komunikasi Keluarga Sebagai Salah Satu Model Pengasuhan Keluarga Bagi Siswa SMP 1, 2, 3 Sukawati Gianyar - N.L.P Yunianti Suntari C; NLK Sulisna Dewi; I Ketut Labir (Jurnal Pengabmas Masyarakat Sehat, 2019)
Children are infinite gifts. They are the next generation of the nation in a country. Children's growth and development is an absolute concern for parents. To achieve good growth and development of children, of course also must be with education and support from the environment where children live. Children are complex creatures who have a high dependence on other people, especially the closest person. Information and guidance for parents, we pack in a simple book, with the titled "Family Communication Module". Become a kind of guidance for families and teenagers, how ideally they interact with each other. Parents are rule models in the family. A good example will reduce good examples of children's development, especially emotional intelligence and independence. Of the 140 respondents, 93 people or 66.43% got good benefits. 37 people or 26.43% get enough benefits, and 10 people or 7.14% have not received significant benefits from the use of this family communication module.Keywords: Children, Family, Communication